Padrão de ocupação de cutias (Dasyprocta azarae) em paisagens neotropicais - Rodrigues, Érick Teixeira [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Impacts of human activities are worldwide known to be the main cause of species extirpation around the globe and the landscape ecology science has proven to be an essential science to help understand and solve this problem. The agouti Dasyprocta azarae (Lichtenstein 1823) is a mammal that inhabits areas of forests along with river courses, this animal is a seed dispersor and an essential prey of a wide range of felids. Even though this agouti specie is essential to maintain ecological process, it suffers impacts of habitat loss and fragmentation, despite being vulnerable to hunting activities of men and predation pressure of feral dogs. For those reasons, this research has as its main goal to understand how landscape structure influences occupancy patterns of agoutis in an ecotone of ecoregions in center-west regions of Brazil. This work states as hypothesis that occupation probability of agouties will be higher in less impacted landscapes. To understand the influences of landscape structure on occupancy probabilities, camera trap data was collected along 20 landscapes distributed through the Mato Grosso do Sul State, Brazil, encompassing different phytogeographic domains. The studied ladnscapes were georeferenced, a circular buffer of two Km was created in each area and was mapped through satellites images using the softwares ArcGIS and QuantumGIS in a cartographic reason 1:2500, later the landscape structure was identified and classified. From the generated maps, landscape metrics were calculated in order to build an occupation model, considering that the detection probability of this agouti specie is less than one (imperfect detection) and may vary across landscapes. Finally, these analyses will be done to different scales in order to find the scale of effect. Finally, the result of this work allows us to infer relations between the landscape metrics and the probability of occupancy, and also between the covariate of detectability and...

Atividades antrópicas são consideradas as principais causas do extermínio de espécies ao redor do planeta e a ecologia de paisagens tem se mostrado uma ciência essencial para entender e solucionar estes problemas. A espécie de cutia Dasyprocta azarae (Lichtenstein 1823) é um mamífero que habita áreas florestais associadas a corpos d'água, importante dispersora de sementes e presa essencial de diversos felinos. Apesar da sua importância ecológica, esta espécie sofre efeitos de perda e fragmentação de habitat, além de estar sujeita à pressão de predação por cães ferais e pressão de caça pelo ser humano. Desta forma, este trabalho tem por objetivo identificar como as características da paisagem se relacionam com o padrão de ocupação de cutias em um ecótono de ecoregiões no centro-oeste brasileiro. Este trabalho tem como hipótese que a probabilidade de ocupação destes animais será maior em paisagens menos alteradas por atividades antrópicas. Para entender a relação entre a estrutura da paisagem e o padrão de ocupação destes animais, dados foram coletados através de armadilhas fotográficas em 20 paisagens distribuídas ao longo do Estado do Mato Grosso do Sul, abrangendo diferentes domínios fitogeográficos. As áreas de estudo foram georeferenciadas, um buffer circular de dois Km ao redor de cada câmera foi criado e mapeado manualmente através de imagens de satélites utilizando os softwares ArcGIS e QuantumGIS na razão cartográfica 1:2500, posteriormente as características das paisagens foram identificadas e classificadas. A partir dos mapas gerados algumas métricas da estrutura da paisagem foram calculadas a fim de compor um modelo ocupacional, levando-se em conta que a probabilidade de detecção da espécie é menor que um (detecção imperfeita) e pode variar entre as paisagens. Finalmente, esta análise foi realizada para diferentes extensões espaciais a fim de encontrar um ponto ótimo de...
Keywords: Ecologia vegetal; Ecologia da paisagem; Cutias; Sementes - Disseminação; Paisagens fragmentadas; Habitat (Ecologia); Brasil, Centro-Oeste; Mato Grosso do Sul